From Willingness to Competence: Investigating Primary Teachers’ Readiness for EMI Implementation - Ratri, Devinta Puspita; Gozali, Agus; Inayati, Dian; Razali, Khairil Azwar Bin (PANYONARA: Journal of English Education, 2025)
English as a Medium of Instruction (EMI) is increasingly promoted in Indonesian primary schools to accelerate bilingual competence, yet evidence on teacher readiness remains limited. This explanatory sequential qualitative-methods study examined the EMI readiness of 108 teachers from elementary schools in East Java. An adapted 16-item EMI-Readiness Scale (α =.89) and three open-ended prompts captured quantitative and qualitative data across knowledge, skills, and attitude dimensions. Descriptive statistics revealed moderate overall readiness: conceptual knowledge (M = 2.75), pedagogical–linguistic skills (M = 2.64), and attitudes (M = 2.88). Only 40 % of teachers felt confident in spoken or written English, and the lowest means concerned oral fluency (2.39) and writing (2.41). Regression analysis showed perceived policy clarity was the strongest predictor of self-efficacy (β = .42, p < .01). Cluster analysis identified three attitudinal profiles—ready-supported (28 %), conditionally willing (46 %), and reluctant (26 %). Qualitative data uncovered reliance on ad-hoc self-learning, resource shortages, and ambivalent sociocultural positioning. The findings highlight a persistent gap between policy aspirations and classroom capability, driven by limited professional development, insufficient language proficiency, unclear guidelines, and infrastructural constraints. The study proposes a phased, resource-backed professional-development agenda that integrates content-language pedagogy, collaborative mentoring, translanguaging scaffolds, and systematic monitoring to foster sustainable EMI implementation.